1996
DOI: 10.1017/s0950268800001564
|View full text |Cite
|
Sign up to set email alerts
|

Foal diarrhoea between 1991 and 1994 in the United Kingdom associated withClostridium perfringens, rotavirus,Strongyloides westeriandCryptosporidiumspp.

Abstract: A case control study of foal diarrhoea in the United Kingdom was carried out over a 3-year period. Clostridium perfringens was significantly associated with foal diarrhoea (Odds Ratio (OR) = 3.0), being isolated from 57% of 421 animals with diarrhoea but from only 27% of 223 healthy foals. Also, C. perfringens was significantly associated with fatal diarrhoea (OR = 4.5). About half of diarrhoea with a fatal outcome was attributable to this organism. The other pathogens significantly associated with diarrhoea w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
93
2
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(106 citation statements)
references
References 20 publications
9
93
2
2
Order By: Relevance
“…They are most commonly caused by Clostridium difficile, Clostridium perfringens, Salmonella spp, rotaviral infections, or can be multifactorial, but the etiology of the disease is undetermined in most of the cases (Netherwood et al, 1996;1998;Frederick et al, 2009). Hence, they represent an interesting research subject for probiotic effectiveness.…”
Section: Clinical Studies In Foalsmentioning
confidence: 99%
“…They are most commonly caused by Clostridium difficile, Clostridium perfringens, Salmonella spp, rotaviral infections, or can be multifactorial, but the etiology of the disease is undetermined in most of the cases (Netherwood et al, 1996;1998;Frederick et al, 2009). Hence, they represent an interesting research subject for probiotic effectiveness.…”
Section: Clinical Studies In Foalsmentioning
confidence: 99%
“…It is well known that healthy equines can harbor C. perfringens type A strains, but studies have shown that diarrheic animals are more likely to be positive for the isolation of this microorganism than healthy horses and foals Ciência Rural, v.45, n.6, jun, 2015. (NETHERWOOD et al, 1996;SCHOSTER et al, 2012;SILVA et al, 2013a). Additionally, the cpb2 gene was found to be more common in horses with intestinal disorders compared with healthy animals or those that were hospitalized for reasons other than intestinal problems (GIBERT et al, 1998;HERHOLZ et al, 1999).…”
Section: Horsesmentioning
confidence: 99%
“…Occasionally, disease in younger and older foals has been reported (Browning et al 1991, Conner andDarlington 1980). The virus is highly contagious and frequently involves multiple animals in a herd (Conner and Darlington 1980); in-contact animals may become subclinically infected (Netherwood et al 1996). The virus has a specific tropism for the mature enterocytes located at the villus tip of the jejunal and ileal mucosa.…”
Section: Rotavirusmentioning
confidence: 99%
“…Clinical signs in these cases reflect the severity of the underlying disease and include colic, alterations in haemogram, electrolyte and acid base status, abnormal peritoneal fluid and intestinal mural emphysema visible on abdominal radiographs or ultrasonographic examination (East et al 1998). However, a large survey including foals less than 1 year of age in the UK indicated that, although the organism was significantly associated with approximately 50% of fatal cases recorded, overall fatality was low and most C. perfringens-associated diarrhoea cases were not severe (Netherwood et al 1998b, Netherwood et al 1996. It is unknown whether this discrepancy indicates an increased pathogenicity of the organism in neonates, as suspected for C. perfringens type C, or whether its high prevalence in normal neonatal foals may simply make it the most readily isolated and therefore most frequently incriminated organism in severe cases of neonatal enterocolitis.…”
Section: Rotavirusmentioning
confidence: 99%